2013
DOI: 10.15288/jsad.2013.74.542
|View full text |Cite
|
Sign up to set email alerts
|

Are Certain College Students Prone to Experiencing Excessive Alcohol-Related Consequences? Predicting Membership in a High-Risk Subgroup Using Pre-College Profiles

Abstract: ABSTRACT. Objective: Previous research identifi ed a high-risk subgroup of students who experience high levels of multiple and repeated alcohol-related consequences (MRC group). Although they consist of 20% of the population and account for nearly 50% of the consequences, the MRC group has not been the focus of etiological or prevention research. The present study identifi ed pre-college profi les of psychosocial and behavioral characteristics and examined the association between these profi les and membership… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 49 publications
2
12
0
1
Order By: Relevance
“…Although the MRC group only accounted for approximately 20% of drinkers, they experienced nearly half of all alcohol-related consequences reported. Further, identification of this high-risk group has been replicated independently with similar proportions of MRC group members and consequences experienced (e.g., Varvil-Weld et al, 2012; 2013). The MRC group’s repeated experience with consequences indicates these students do not modify their behavior to avoid subsequent problems, making them important targets for early intervention.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Although the MRC group only accounted for approximately 20% of drinkers, they experienced nearly half of all alcohol-related consequences reported. Further, identification of this high-risk group has been replicated independently with similar proportions of MRC group members and consequences experienced (e.g., Varvil-Weld et al, 2012; 2013). The MRC group’s repeated experience with consequences indicates these students do not modify their behavior to avoid subsequent problems, making them important targets for early intervention.…”
Section: Introductionmentioning
confidence: 85%
“…For example, students who engaged in more risk behaviors (i.e., participated in drinking games) and who had higher perceived drinking norms and rates of weekly and peak drinking were likely to be in the MRC group at the end of their first year in college (Varvil-Weld et al, 2013). Additional research showed an association between parents who exhibited permissive orientations toward underage student alcohol consumption and MRC group membership, again identified at the end of the first year in college (Varvil-Weld et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…As person-centered approaches in the study of alcohol consumption gain traction (e.g., Cleveland et al, 2013;Huh et al, 2013;Varvil-Weld et al, 2013), more research is needed to identify distinct subgroups of young adults at risk for dysfunctional drinking behaviors. As part of this effort, more attention must be paid to race and other differences that may signify different levels of risk, as well as potentially unique mechanisms by which to prevent heavy drinking.…”
Section: Future Directionsmentioning
confidence: 99%
“…Studies in many countries show decreased alcohol use among adolescents and young adults associated with either higher levels of parental monitoring (1,616) or good family relations (1,2,911,1721). A few studies also show higher levels of parental monitoring or stronger family relations protective for alcohol-related consequences among young people (15,22,23). …”
Section: Introductionmentioning
confidence: 99%